The Call for Parent Involvement in Rural Communities: Mantra and Mystification - Aimee Howley; Robert Bickel; Mary McDonough (Journal of Research in Rural Education, 1997)
Taking a critical perspective on the literature that calls for greater parent involvement in rural schools, this study analyzes the relationship between place ofresidence (rural, urban, suburban) and levels ofparent involvement in schools. Invoking a series of relevant individual and contextual control variables, we find that parent involvement in schools varies little in relationship to place ofresidence. Moreover, the negligible effects of the control variables suggest that parent involvement in schools is an elusive phenomenon, perhaps summoned up prematurely as a remedy for low achievement levels in impoverished rural schools. As a consequence, the califor increased parent involvement ought to be treated with circumspection. This caution is particularly germane in light ofthe strong ties that already exist-or once existedbetween residents in many rural communities and their small, local schools. Efforts, both recent and historical, to remove small schools from their local communities seem to run counter to the rhetoric calling for increased levels of parent involvement.